2007
DOI: 10.1186/bf03352059
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the concept of Sudden Storm Commencements and their operative identification

Abstract: In this paper, we review the evolution of both, the concept and the operative methods of detection of Storm Commencements (SC's) and we introduce suggestions for future improvements. Finally, a more precise definition of the events with consequences in terminology and detection is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 93 publications
2
71
0
Order By: Relevance
“…The conditions in the solar wind that lead to enhancement of the ring current are often preceded by a solar wind shock, so the characteristic Sym-H signature of a geomagnetic storm is a positive perturbation (the storm initial phase), a rapid negative excursion lasting several hours (the storm main phase) as the ring current builds, followed by a several-day return to quiescent conditions (the storm recovery phase). The shock arrival and positive excursion of Sym-H is also known as a sudden storm commencement (e.g., Curto et al 2007). There is some evidence for feedback between the intensity of the ring current and the deflation of the magnetotail lobes during the storm recovery phase (Milan 2009;Milan et al 2009a,b).…”
Section: Magnetospheric Dynamicsmentioning
confidence: 99%
“…The conditions in the solar wind that lead to enhancement of the ring current are often preceded by a solar wind shock, so the characteristic Sym-H signature of a geomagnetic storm is a positive perturbation (the storm initial phase), a rapid negative excursion lasting several hours (the storm main phase) as the ring current builds, followed by a several-day return to quiescent conditions (the storm recovery phase). The shock arrival and positive excursion of Sym-H is also known as a sudden storm commencement (e.g., Curto et al 2007). There is some evidence for feedback between the intensity of the ring current and the deflation of the magnetotail lobes during the storm recovery phase (Milan 2009;Milan et al 2009a,b).…”
Section: Magnetospheric Dynamicsmentioning
confidence: 99%
“…This means the first thing from a CME that strikes the magnetosphere is the shock. The shock compresses the magnetosphere, which produces a spiky increase in Dst, known as the storm sudden commencement (SSC) because a geomagnetic storm usually follows (Curto, Araki & Alberca 2007, and references therein). Shocks take anywhere from ∼19 hours to more than four days to reach Earth, as can be seen in Fig.…”
Section: Cme Structure and Geomagnetic Stormsmentioning
confidence: 99%
“…Our main priority is to detect storms that are likely to lead to notable consequences on Earth, such as GIC. In this study, we consider only storms that fulfill the following criteria [similar to those suggested by Joselyn and Tsurutani (1990) and Curto et al (2007) in their quantitative definitions of SSCs]:…”
Section: Defining Geomagnetic Storms and Stormy Conditionsmentioning
confidence: 99%